NEEDS ASSESSMENT AND GUIDELINES FOR COACHING OF SCHOOL ADMINISTRATORS IN SCHOOL UNDER LAMPANG PRIMARY EDUCATIONAL SERVICE AREA OFFICE 2 - Appama, Kanokporn; Thienpraphaku, Panatanon (Academic Journal Phranakhon Rajabhat University, 2024)
The research aimed to study: 1) the necessity of coaching for school administrators in schools under Lampang Primary Educational Service Area Office 2, and 2) the coaching guidelines of school administrators. The population consisted of 764 teachers from schools under the Lampang Primary Educational Service Area Office 2 and 60 school administrators. The samples included 262 teachers and 20 school administrators, totaling 282 individuals. The research tools included a 5-point Likert scale questionnaire on coaching of school administrators, and group conversation record forms. Data analysis employed basic statistics, including percentage, mean, standard deviation, necessity index values, and content analysis. The research findings revealed that: 1) the necessity of coaching for school administrators in schools under Lampang Primary Educational Service Area Office 2 was ranked first in the index of necessity for the process of monitoring emotion and determination, and 2) the coaching guidelines for school administrators in monitoring emotion and determination involved asking questions to determine the dedication score, ranging from 0 to 10. Administrators must instill confidence in teachers within the school.